Genes of ACYL CARRIER PROTEIN Family Show Different Expression Profiles and Overexpression of ACYL CARRIER PROTEIN 5 Modulates Fatty Acid Composition and Enhances Salt Stress Tolerance in Arabidopsis - Huang, Jiexue; Xue, Caiwen; Wang, Han; Wang, Lisai; Schmidt, Wolfgang; Shen, Renfang; Lan, Ping (Frontiers in Plant Science, 2017)
Acyl Carrier Proteins (ACPs) are a group of small acidic proteins functioning as important cofactors in the de novo synthesis of fatty acids. In Arabidopsis, ACPs are encoded by a small gene family comprising five plastid members, AtACP1 to AtACP5, and three mitochondrial members. The biological functions and the transcriptional responses to abiotic stresses of most AtACPs have yet to be elucidated. The present study extends previous findings and provides new knowledge on the function of ACPs by examining the responses of AtACP-encoding genes to several abiotic stresses and, in particular, the role of AtACP5 in the adaptation to salt stress. Phylogenetic analysis showed that AtACP1, AtACP2, AtACP3 and AtACP5 can be classified into one group and separated from a group comprising AtACP4 and ACP homologs from related species. Quantitative RT-PCR analysis revealed that the expression of AtACP1, AtACP2 and AtACP3 was induced by drought. Both iron deficiency and nitrogen starvation resulted in down-regulation of AtACP4. The most pronounced response was observed for AtACP5, the expression of which was dramatically decreased by salt stress. Knock-out of AtACP5 showed increased sensitivity to NaCl stress, whereas transgenic lines overexpressing AtACP5 displayed increased salt tolerance relative to the wild-type. Overexpression of AtACP5 further led to an altered composition of fatty acids, mainly a decrease of oleic acid (C18:1) and an increase of palmitic acid (C16:0), and to a lower Na+/K+ ratio when compared to the salt stressed wild-type. The comprehensive transcriptional information on the small plastid AtACP gene family in response to various abiotic stresses and the further investigation of the AtACP5 indicate that AtACP5 might be critical for salt tolerance through alterations of the composition of fatty acids and, subsequently, the Na+/K+ ratio.